2017
DOI: 10.1093/ecco-jcc/jjx163
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Outcomes in Ustekinumab-Treated Patients Undergoing Abdominal Operations for Crohn’s Disease

Abstract: Of the 44 patients with CD who received ustekinumab within the 12 weeks prior to a major abdominal operation, 13% experienced a 30-day postoperative SSI, not statistically different from the 20% found in the anti-TNF cohort. Ustekinumab treatment within 12 weeks of surgery does not appear to increase the risk of postoperative SSI above that of CD patients treated with anti-TNF medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 23 publications
2
47
0
3
Order By: Relevance
“…Perioperative safety outcomes of patients exposed to ustekinumab were assessed in two retrospective multicenter cohort studies. 60,61 Ustekinumab use was not observed, in both studies, to be associated with the increased risk of postoperative surgical site infection when compared with anti-TNF-treated patients. This is in spite of a higher use of concomitant immunosuppressants in the ustekinumab group in the study by Shim et al The study by Lightner et al, however, noted an increased risk of reoperation in the ustekinumab cohort.…”
Section: Safety Of Ustekinumab In Special Populationsmentioning
confidence: 71%
See 1 more Smart Citation
“…Perioperative safety outcomes of patients exposed to ustekinumab were assessed in two retrospective multicenter cohort studies. 60,61 Ustekinumab use was not observed, in both studies, to be associated with the increased risk of postoperative surgical site infection when compared with anti-TNF-treated patients. This is in spite of a higher use of concomitant immunosuppressants in the ustekinumab group in the study by Shim et al The study by Lightner et al, however, noted an increased risk of reoperation in the ustekinumab cohort.…”
Section: Safety Of Ustekinumab In Special Populationsmentioning
confidence: 71%
“…Perioperative safety outcomes of patients exposed to ustekinumab were assessed in two retrospective multicenter cohort studies . Ustekinumab use was not observed, in both studies, to be associated with the increased risk of postoperative surgical site infection when compared with anti‐TNF‐treated patients.…”
Section: Ustekinumabmentioning
confidence: 99%
“…However, two systematic reviews and meta-analysis [27,28] did not find increased risks of postoperative complications with the use of vedolizumab when compared to either preoperative anti-TNF therapy or no biological therapy. Studies regarding the use of ustekinumab comparing with anti-TNF therapy also demonstrated no increase in the risk of postoperative complications [29,30].…”
Section: Biological Therapy and Surgerymentioning
confidence: 99%
“…There are minimal data on infectious risk with ustekinumab. A small retrospective study has shown that the 30‐day infectious complication rate after abdominal surgery for Crohn's disease in patients who received ustekinumab within 12 weeks prior to surgery was 13%, not dissimilar from patients who received anti‐TNF therapy .…”
Section: Impact Of Medication On Surgery For Ibdmentioning
confidence: 99%